Pais presentes, pais ausentes: uma análise das redes de suporte material e de cuidado de crianças de um grupo de mães adolescentes em Quito - Pilar Carolina Posso Ruiz (2014)
Ecuador is one of the countries in Latin America with the highest teenage fertility rates. Policies seek primarily to prevent pregnancy during the adolescence. In the country, little is known about teenage mothers children material and care support networks. On the other hand, those childrens fathers are a poorly studied population, as well as the ways in which they exert paternity. The aim of this dissertation is to study the composition of material and care support networks of a group of teenage mothers in Quito, and analyze the role that those childrens fathers have, in those networks. Support is studied from the social capital theory. This approach affirms that resources are embedded in social networks and are accessed by the actors through their relationships. To achieve the objectives of the dissertation, 50 mothers aged 12-19 years, who were living in Quito, were studied. The information was gathered through interviews. The field research was conducted between October 2013 and January 2014. These are the main results. Ties strengthens of kinship relationships and spatial distance are aspects that influence support. Childcare is performed, especially, by women. The main actor in the material support and care networks is the teenage family of origin, especially, the childs maternal grandmother. Other important actors in the material support and care networks are members of the teenage mothers extended family. Childs father and his family of origin are part of the support networks, mainly the material support. Fathers extended family has little involvement in support networks. Girlfriends and institutional actors contribute with support, in cases of teens who belong to protective homes. Childs father and his family of origin support are associated with affective ties in father-adolescent mother dyadic. People who are part of material and care support networks have higher "popularity" in the teenage mothers social network, measured by centrality degree. Fathers who give care and material support, from Monday to Friday, have greater centrality in the social network, compared to those who do not give support. For interviewed mothers, the ideal of fatherhood is related with the expression of affections, care and economic support. The results of the dissertation provide elements for public policies to go beyond the prevention of teenage pregnancy and consider other actors that contribute with child support.